Water and inoculation method affect germination and penetration by Ciborinia camelliae - Vingnana-Singam, V.; Long, P.G.; Rowland, R.E. (New Zealand Plant Protection, 2001)
Possible interactions between free water and methods of inoculating camellia petals with Ciborinia camelliae were investigated Spore suspensions were applied by pipette or atomiser while nonaqueous applications were made with a paintbrush or gravitational deposition from an apothecium Most spores germinated and penetrated the cuticle with pipetted spore suspensions or with gravitional deposition from an apothecium Brush and spray applications resulted in less germination and fewer infections Drying petal tissue before incubation in humid chambers reduced germination penetration and development of symptoms If water was added to petals with brush applied spores then multiple germ tubes and swollen hyphae were common and many germ tubes grew across the petal surface without penetrating